Building approval procedure / Nurul Syafiqah Mohamad Rosidi - Mohamad Rosidi, Nurul Syafiqah (Universiti Teknologi MARA UiTM,Perak, 2021)
Building plan approval is very important in order to do some construction works for example housings, shops and more. Majlis Perbandaran Kota Bharu is one of the places where the applicant applies for building approval. For those who wants to apply building plan approval must follow all the terms and specification that municipality provide. For example, submit RC plan, follow the side back of the building that required in Uniform Building By-Law 1984 and more. The objective of this case study is to determine the procedure that applicants need to apply building plan approval. The procedure is very easy if the applicants follow all the specification that municipality need and if the applicants did not cooperate with the municipality, the application for approval of the building became slow, and the construction could not be built. After that, assistant engineer will identify the problem and solution by visit to the construction site and inspect the construction work. If there are some problems if the applicants did not follow the terms that provided, municipality will impose a compound on the applicant for violating the stipulated conditions. So, this report is about the procedure of building plan approval to build and complete 1 unit of 1 storey house, Lot PT 470, section 35, Mukim Semut Api, Kota Bharu. There are three stages in the building approval application process. From the online application process to the process to claim a deposit and certificate of eligibility to sit CCC.